Characterization of the upper respiratory tract microbiome of patients with acute respiratory infections by 16S rRNA sequencing - A. A. Ivanova; A. A. Perederiy; A. S. Popenko; E. V. Venev; A. V. Fadeev; D. A. Gusev; D. M. Danilenko; A. B. Komissarov; D. A. Lioznov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. Acute respiratory infections (ARI) are one of the main causes of morbidity and mortality from infectious diseases in the world. Respiratory infections can be caused by pathogens of various etiologies: viruses, bacteria, mycoplasmas, etc. Rapid and accurate identification of pathogens, such as bacteria, in biological samples is an important task, for which 16S rRNA gene sequencing using new generation platforms is used.The objective was a comparative analysis of the qualitative characteristics of the oropharyngeal microbiome of healthy volunteers and patients with ARI of unknown etiology based on the 16S rRNA gene sequencing.Methods and materials. Using V3–V4 region of 16S rRNA Illumina MiSeq sequences from oropharyngeal swabs, we analyzed the microbiome of hospitalized patients with ARI symptoms and healthy patients.Results. In this study, we conducted V3–V4 region of 16S rRNA sequencing analyses of the oropharyngeal samples from 116 hospitalized patients with ARI symptoms and 81 healthy patients. Patients with ARI exhibited higher abundance of opportunistic pathogens, particularly Staphylococcus, Ralstonia, Aeribacillus, Acinetobacter baumannii, Methylobacterium-Methylorubrum, Rhodococcus equi. In the control samples, normal commensal respiratory tract microbiota, such as Neisseria, Prevotella, Fusobacterium, Veilonella was dominated.Conclusions. The microbiota samples of hospitalized patients with ARI showed a predominance of opportunistic and potentially pathogenic microbiota, while normal representatives of the respiratory tract microbiota predominate in healthy volunteers. For a more detailed analysis, data on the species composition of the microbiota is required, which can be obtained by sequencing the complete sequence of the 16S rRNA gene.